Untersuchungen zur Aufzucht von Dorschen (Gadus morhua morhua) der Westlichen Ostsee. Teil II: Aufbau und Hälterung eines Laichfischbestandes sowie Erbrütung der gewonnenen Eier - Bleil, Martina (1995)
In 1993 and 1994 hatching and rearing of cod eggs and larvae from the western stock was carried out aiming at data about the reproduction biology of this species. This paper describes the hatching methods and first results of the correlation between various biotic and abiotic factors, naturally fertilized eggs from a broodstock, and the amount of viable larvae.